LUGAR QUE A ESCOLA OCUPA PARA ALUNOS DO ENSINO FUNDAMENTAL: MOTIVOS PARA SUA PERMANÊNCIA NESSE ESPAÇO (Revista Contexto & Educação, 2021)
Analyzing the context of liquid modernity, it is possible to observe that the school has been receiving an increasingly heterogeneous group of students, characterized by social, cultural, economic, political, ethnic and gender diversity. It is in this place marked by differences that young people spend part of their time, establish emotional bonds and share experiences, giving reasons for staying there. Considering that education is highlighted by many young people as a mean to overcome social boundaries, the aim of this article is to analyze the reasons, attributed by students who attend elementary school, for their permanence in school. The article is based on empirical research with a qualitative approach. Data collection took place using the Focus Group technique, and the analysis used the Discursive Textual Analysis methodology. The data revealed that the main incentives listed by young people about staying in school are good teachers and parents.